2016
DOI: 10.1002/2015wr017805
|View full text |Cite
|
Sign up to set email alerts
|

Methane occurrence is associated with sodium‐rich valley waters in domestic wells overlying the Marcellus shale in New York State

Abstract: Prior work suggests spatial parameters (e.g., landscape position, distance to nearest gas well)can be used to estimate the amount of dissolved methane in domestic drinking water wells overlying the deep Marcellus Shale. New York (NY) provides an opportunity to investigate methane occurrence prior to expansion of high-volume hydraulic fracturing because unconventional gas production is currently banned in the state. We sampled domestic groundwater wells for methane in 2013 (n 5 137) across five counties of NY b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Note that the amount of methane for samples >20 mg/L is only semiquantitative because of the sampling methodology at approximately atmospheric pressure (Molofsky et al ). Several authors (Wardrop ; Christian et al ; Loomer et al ) have documented seasonal and other temporal variations of dissolved methane but the variations rarely show large swings from high methane to none. Resampling of several wells two or three times, particularly in the Parker County area, showed good agreement between sampling events with no dramatic change, that is, individual wells may display some variations but the variations will not impact the interpretation of results, which rely on aggregate not on results of a specific well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the amount of methane for samples >20 mg/L is only semiquantitative because of the sampling methodology at approximately atmospheric pressure (Molofsky et al ). Several authors (Wardrop ; Christian et al ; Loomer et al ) have documented seasonal and other temporal variations of dissolved methane but the variations rarely show large swings from high methane to none. Resampling of several wells two or three times, particularly in the Parker County area, showed good agreement between sampling events with no dramatic change, that is, individual wells may display some variations but the variations will not impact the interpretation of results, which rely on aggregate not on results of a specific well.…”
Section: Resultsmentioning
confidence: 99%
“…Several research papers documented the initial state of knowledge on dissolved methane distribution in groundwater (Osborn et al 2011;Jackson et al 2013a;Molofsky et al 2013). These initial studies were quickly followed by others in Pennsylvania (Heisig and Scott 2013;Baldassare et al 2014;Darrah et al 2014;Wilson 2014;Siegel et al 2015Siegel et al , 2016Christian et al 2016) and elsewhere: Colorado (Li and Carlson 2014;Sherwood et al 2016), Fayetteville in Arkansas (Warner et al 2013), Bakken in North Dakota (McMahon et al 2015), Texas (Nicot et al 2015(Nicot et al , 2017a(Nicot et al , 2017bWen et al 2016), and Canada (Cheung et al 2010;Moritz et al 2015;Humez et al 2016). The source of the dissolved methane is sometimes clear, in particular when it is microbial (Warner et al 2013;McMahon et al 2015) but still the object of conflicting studies when mostly thermogenic, such as in Pennsylvania (Jackson et al 2013a;Molofsky et al 2013;Darrah et al 2014) or Texas (Darrah et al 2014;Wen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Marcellus Shale in the northeastern United States, Osborn et al (), Jackson et al (, ), and Ingraffea et al () concluded that at least some of the shallow methane was sourced from leaky gas wells. Conversely, Molofsky et al (), Siegel et al (, ), Christian et al (), and some U.S. Geological Survey (USGS) authors, Heisig and Scott () in central New York state and White and Mathes () in West Virginia, stated that the presence of thermogenic methane is mostly natural and correlated with the topography. Other studies either did not find elevated methane concentrations or established that the methane was of microbial origin.…”
Section: Introductionmentioning
confidence: 99%
“…In a few studies, such as in the Marcellus and Barnett Shales, conflicting interpretations have been advanced. There, some authors favor a natural origin (Molofsky et al ; Siegel et al ; Christian et al ; Siegel et al ; Wen et al ; Nicot et al 2017a, 2017b), whereas others support an anthropogenic origin attributed to oil and gas activities, at least in part (Warner et al ; Jackson et al ; Darrah et al ). The objective of this study was to determine controls on methane occurrences in aquifers in the Eagle Ford Shale play footprint, that is, whether the presence of dissolved methane in shallow groundwater and drinking water aquifers results from natural processes or hydraulic fracturing activity.…”
Section: Introductionmentioning
confidence: 99%